The impact of diabetes mellitus type 2 on the steroidogenesis of male Zucker Diabetic Fatty rats - Benko, F; Chomová, M; Uličná, O; Ďuračka, M; Kováč, J; Tvrdá, E (Physiological research, 2022)
The aim of this study was to evaluate the impact of diabetes mellitus type 2 (DM2) on the male endocrine system of Zucker Diabetic Fatty (ZDF) rats. Sexually mature ZDF rats were divided to a lean (control) and obese group, and had diabetes confirmed by blood tests. For the in vivo experiment, fasting blood was collected to obtain blood plasma. In case of the in vitro experiments, testicular fragments were cultured for 24 h, and the culture medium was collected. The concentrations of testosterone (T), androstenedione (A4), dehydroepiandrosterone (DHEA-S), estradiol (E2), follicle-stimulating hormone (FSH) and luteinizing hormone (LH) were quantified in the blood plasma and the medium by the ELISA method, while cholesterol (CHOL) was assessed spectrophotometrically. A significant decline of T (36.31 %), A4 (25.11 %) and FSH (26.99 %) as well as a significant increase of CHOL and E2 (36.17 %) was observed in the blood plasma of obese ZDF rats in comparison to the control. Under in vitro conditions, a significant decrease of FSH (23.35 %) accompanied by an increase of E2 was observed in the obese group compared to the control. In the case of CHOL, LH, T, DHEA and A4 no significant differences were observed. Our results suggest that except for FSH and E2 all steroid biomolecules were synthetized normally by the testicular tissue, however a dramatic endocrine disturbance was observed at the system level. We may conclude that DM2 has negative effects on systemic hormone secretion and these alterations are more pronounced in combination with obesity.
Keywords: obezita; Rats, Zucker; estradiol; luteinizační hormon; krysa rodu Rattus; Follicle Stimulating Hormone; folikuly stimulující hormon; zvířata; Diabetes Mellitus, Type 2; Luteinizing Hormone; Estradiol; Male; Testosterone; Rats; Obesity; Animals; mužské pohlaví; testosteron; diabetes mellitus 2. typu; dehydroepiandrosteron; potkani Zucker; Dehydroepiandrosterone